QUALITY ASSURANCE AUDIT OF INTRA-ORAL PERIAPICAL RADIOGRAPHS AT THE UNDERGRADUATE DENTAL SCHOOL - Khan, Anum; Javed, Muhammad Qasim; Iqbal, Rida; Khan, Fareeha; Habib, Syed Rashid (Journal of Ayub Medical College Abbottabad, 2020)
Background The three fundamental principles of radiation protection are justification, dose optimization or limitation and subsequently following the As Low as Reasonably Practicable- (ALARP) principle. Quality assurance (QA) program for dental radiography is important in order to yield results with maximum diagnostic value, minimize errors, aid in interpretation, avoid unnecessary repetition of radiographs and therefore, additional radiation exposure. Methods This standard based audit was conducted at an undergraduate and postgraduate teaching hospital. One thousand and sixty four intra oral periapical radiographs were graded according to the set standards by NRPB by 3 examiners. Data were analyzed with SPSS-24. Results Out of the 532 conventional periapical radiographs, 313 radiographs were Grade 1, 177 radiographs were Grade 2 and 42 radiographs were Grade 3, requiring a repeat radiograph. For 532 digitally taken periapical radiographs, 255 radiographs were Grade 1, 192 radiographs were Grade 2 and 85 radiographs were Grade 3 and diagnostically unacceptable. Considering the aforementioned results, the findings of the first cycle did not meet the standards. Conclusion According to the results of the quality assurance audit, the radiographs were below the standards set by NRPB. Recommendations were made for improvement measures in the radiology department and plan to re-audit after six months. Keywords: Radiographs, Quality Assurance; Audit